Evaluasi Kualitas, Kuantitas Telur Dan Larva Ikan Patin Siam (Pangasianodon Hiphopthalmus) Dengan Penambahan Ovaprim Dosis Berbeda - Manantung, Vina O; Sinjal, Hengky J; Monijung, Revol D (e-Journal BUDIDAYA PERAIRAN, 2013)
This study was conducted to determine the effect of different doses of ovaprim on latency time of spawning, hatching rate, and survival of fish larvae (Pangasianodon hiphopthalmus). Experimental design used was Randomized Complete Design (CRD) with four treatments, each with three replication. The treatments including 0 ml, 0.3 ml, 0.6 ml and 0.9 ml ovaprim per kg of body weight of fish. Data collected consisted of latency time of spawning, hatching rate, and survival rate of larvae. The results showed that treatment with different doses of ovaprim hormones resulted in a significant influence on latency time of spawning, egg hatchability and survival rate of larvae. It was found that 0.6 ml ovaprim could increase the latency time of spawning, egg hatchability and survival rate of larvae. The average latency time of larvae was 529 minutes, hatching rate was 80,86% and survival rate of larvae was 83,33%.